ANALISIS PENDAPATAN DAN POLA KEMITRAAN AGROINDUSTRI TEMBAKAU VIRGINIA DI KABUPATEN BULELENG - Ni Luh Riana Dentika Utami; Cening Kardi; Putu Fajar Kartika Lestari (AGRIMETA : Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2018)
Buleleng Regency is one of the centers of Virginia tobacco production in Bali, which is a partnership with Gudang Garam and Beringin Bali. The purpose of this study was to (1) analyze the input and output of Virginia tobacco enterprises in Buleleng District and, (2) to analyze the financing and income of the phases of the production process of virginia tobacco business, (3) to analyze the partnership process between Gudang Garam and Beringin Bali as a partner company with Virginia tobacco farmers in Buleleng District. This research was a quantitative and qualitative research, data obtained based on interviews and obtained from government institutions. All Virginia tobacco business in Buleleng Regency was taken 4 informants (purposive sampling). From the results of this study can be drawn conclusion as follows. Productivity of Virginia tobacco agro-industry in Buleleng Regency with a land area of 1 hectare per season. Productivity in Desa Sawan is 3,789 kg / ha of wet tobacco to 2,880 kg / ha of dry tobacco, while productivity in Baktiseraga village is 3,825 kg / ha of wet tobacco to 2,713 kg / ha of dry tobacco; Virginia tobacco farming income in Sawan Village amounted to Rp.633.000 with RC ratio 1.02 whereas in Baktiseraga Village Rp.859.000 with RC ratio 1.03. In the income of tobacco farming in Buleleng regency can be considered profitable but the income can not be able to return the cost of farming; The income of tobacco oven in Sawan Village is Rp.46,988,500 with RC ratio 1.97 (advantageous), whereas in Baktiseraga Village, the business income of the oven is Rp.46.185.500 with RC ratio 2.00 (favorable); The pattern of partnership that exists is the core pattern of plasma and subcontract, where farmers only sell tobacco harvest to the factory. The selling price of tobacco leaves has been determined by the factory. Meanwhile, all the needs during the production process are prepared independently by the farmers in accordance with the terms desired partners. The 13,000 seeds are given free to tobacco farmers in Sawan Village and Baktiseraga Village by Gudang Garam and Beringin Bali. Based on some findings in this study can be suggested as follows. Virginia tobacco farmers to increase their tobacco production capacity per hectare. For resting tobacco farmers to start re-planting tobacco; The partnership pattern that exists between the farmers and the Gudang Garam and Beringin Bali companies can be established better and equally beneficial without harming one another. There should be a written agreement between farmers and companies to provide assurance of price assurance for farmers and product certainty for the company.